PENGARUH KOMPETENSI GURU DAN MOTIVASI KERJA TERHADAP KINERJA GURU DIMEDIASI KEPUASAN KERJA DI KECAMATAN SAYUNG KABUPATEN DEMAK TAHUN PEMBELAJARAN 2011 / 2012 - Murdiyati, Sri (Students Journal of Economic and Management, 2012)
The purpose of this study to determine examining the influence of satisfaction, motivation and competence of teachers on teacher performance of teachers to the performance of job satisfaction mediated Research conducted Teacher Job Satisfaction Performance in Sub Sayung Demak Implementation Year 2011/2012. The study population was all public primary school teachers Technical Unit Department of Education, Youth and Sports sub Sayung Demak numbering 343 people scattered in 44 schools. The sampling technique used is proportional random sampling, the samples were taken by 78 teachers, The variables are labor discipline and motivation, principal leadership and teacher performance. Data analysis techniques in this study using regression analysis and hypothesis testing moderation calculation t test at significance level of 5%. Competency of teachers effect on job satisfaction of teachers. Work motivation effect on job satisfaction of teachers. Competence teacher effect on the performance of teachers. Motivation effect on the performance of teachers. Job satisfaction effect on the performance of teachers. Keywords : Teacher Competency, Motivation, Performance, Job Satisfaction